Mapping the Research Theme and Method: A Corpus Based to Abstract of Arabic Education Undergraduate Program - Arifa, Zakiyah; Al Faruq, Umar (Arabiyatuna: Jurnal Bahasa Arab, 2021)
This research aims to describe the research themes and methods most in-demand and explain the representation of research mapping in the Arabic Education undergraduate program in Universitas Islam Negeri Maulana Malik Ibrahim Malang through linguistic corpus analysis. This study is essential to provide a real portrait of the reality of research trends among students. A quantitative approach is used to describe the frequency of words based on the Antconc application's linguistic corpus. Meanwhile, a qualitative approach is used to represent the meaning of corpus-based findings. The data are taken from Arabic abstracts on digital library. The results showed that the research theme most interested chosen by students in the last 5 years was the learning cluster, namely materials and textbooks, the language skills cluster, namely speaking skills, and the language element cluster, namely vocabulary. This shows that students tend to research vocabulary-based speaking skills material. The research method most widely used by students is Research and Development (R&D). Students tend to develop teaching materials or dictionaries, which are a trend of research methods. These mapping results are expected to be material for evaluation to determine the Arabic language research policies for lecturers and departments. For students and further researchers, it can be used as a basis and consideration for the description of the state of the art in choosing themes and research methods.